Orthovanadate nanoparticles delay the accelerated aging in rats via the prevention of oxidative disturbances - Nikitchenko, Yu.V.; Klochkov, V.K.; Kavok, N.S.; Karpenko, N.A.; Sedyh, O.O.; Bozhkov, A.I.; Malyukin, Yu.V.; Seminozhenko, V.P. (Доповіді НАН України, 2020)
The abilities of gadolinium orthovanadate nanoparticles (GdVO₄ : Eu³⁺ NPs, 8x25 nm) to ameliorate age-related lesions have been studied. To achieve the goal, a model of accelerated aging due to postnatal overfeeding (POF) was used. The features of the model are oxidative misbalance and decrease in survival, as well as adverse metabolic effects. The NPs were orally administrated (briefly or continuously) with drinking water to rats with accelerated aging. Then the prooxidant-antioxidant balance (in liver and blood), survival, and life expectancy were examined. In young (3 months-old) rats with accelerated aging, already the short-term (2 months) NPs implementation significantly corrects the oxidative disturbance. The prolonged use of NPs from 11 to 31 months of life ameliorates significantly the prooxidant-antioxidant misbalance in the liver and blood of POF rats. Wherein, the observed median of survival in the control group is 890 days, in the group with accelerated aging — only 710 days, while the additional receive of NPs increases the score — already 940 days. Furthermore, the death of the last animal in the control group is observed by day 1130, at accelerated aging — by day 1000, and at accelerated aging with additional NPs using — by day 1250. Thus, the both indicators — the survival and the lifespan, are increased due to the NPs applications by 32 % and 25%, respectively, compared with the accelerated ageing group, which receives no NPs. The obtained data show that the prolonged GdVO₄ : Eu³⁺ NPs application in animals with experimental accelerated aging corrects the oxidative misbalance as well as increases the survival of elderly animals. Discovered effects make these nanoparticles a promising geroprotective agent, decreasing the risk of increased mortality and morbidity at premature ageing — adverse consequences of the overnutrition in early life.